Analisis Penerapan Akuntansi Syariah dalam Praktik Bisnis: Studi Deskriptif Kualitatif pada Entitas Berbasis Syariah - JEPRI JEPRI; Wan Febri Juniati; Fatimah Zaharah (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This study aims to analyze the application of sharia accounting in business practices in sharia-based entities. The approach used is descriptive qualitative, with in-depth interview methods and document analysis as data collection tools. The results of the study indicate that the application of sharia accounting in the entities studied has reflected sharia principles, such as fairness, transparency, and social responsibility. However, there are obstacles in the implementation, such as limited human resources who understand sharia accounting in depth. This study is expected to contribute to the development of sharia accounting practices in Indonesia.